Electronic Nutrition (e-Gizi) Application Development on RSUP Dr. Mohammad Hoesin Palembang Using the Rapid Application Development Method - Muhammad Haykal Alfariz Saputra; Ahmad Haidar Mirza (Journal of Information System and Informatics, 2022)
Regional General Hospital Dr Mohammad Hoesin Palembang is one of the types A vertical hospitals in Palembang. Patients who come are not only from South Sumatra but also from outside the region. Dr Mohammad Hoesin Hospital has inpatient services. One of the inpatient facilities is providing food which will be divided into 3 shifts. Currently, data gathering on the patient diet is performed manually, which indicates that many patients have returned home but somehow the food has been made, and the natural ingredients at the nutrition establishment do not match what would be in it. A solution that can facilitate the distribution of food at Dr Mohammad Hoesin Hospital and make it easier to record the patient's diet is to build a website-based Electronic Nutrition (e-Gizi) application.